2022
DOI: 10.3389/fsurg.2022.989204
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in cancer-specific survival for locally advanced esophageal cancer after neoadjuvant chemoradiotherapy: A population-based analysis

Abstract: ObjectiveNeoadjuvant chemoradiotherapy (nCRT) is the recommended standard treatment for locally advanced esophageal cancer (LA-EC). This study aimed to determine whether sex makes a difference in cancer-specific survival (CSS) and construct a novel nomogram model to predict CSS for LA-EC after nCRT based on the SEER database.MethodsPatients coded by 04–15 were identified from the SEER database. Patients with systemic treatment and radiotherapy before surgery were defined as nCRT. We further divided this popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[36] Likewise, another study also found that sex was a prognostic factor for esophageal squamous cell carcinoma, but not adenocarcinoma. [37] It not clear why women have a better prognosis. One possible biological mechanism for the sex difference is the effect of estrogen, which inhibits the growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Likewise, another study also found that sex was a prognostic factor for esophageal squamous cell carcinoma, but not adenocarcinoma. [37] It not clear why women have a better prognosis. One possible biological mechanism for the sex difference is the effect of estrogen, which inhibits the growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Multiple studies have consistently reported better response rates and prolonged survival among women undergoing anticancer treatments, including nCRT. [24][25][26][27][28][29] Inititally, these beneficial outcomes were ascribed to reduced exposure to risk factors or enhanced pharmacokinetic drug handling. However, accumulating evidence underscores the role of sex-dependent immunity.…”
Section: Introductionmentioning
confidence: 99%